2021
DOI: 10.1002/cbin.11622
|View full text |Cite
|
Sign up to set email alerts
|

Mini‐patient‐derived xenograft assay based on microfluidic technology promises to be an effective tool for screening individualized chemotherapy regimens for advanced non‐small cell lung cancer

Abstract: Patient‐derived xenograft (PDX) assay has been widely used in preclinical research in patients with multidrug‐resistant lung cancer. One hundred patients with non‐small cell lung cancer (NSCLC) were divided into MiniPDX group and conventional group, with 50 cases in each group. The MiniPDX assay was established by enriching high‐purity tumor cells using microfluidic technology to detect the drug sensitivity of NSCLC cells. All patients underwent conventional computed tomography (CT) scans of lung and mediastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Also, the study by Yang et al showed a significant benefit from the MiniPDX test than the control group in hepatocellular carcinoma (DFS: 25.8 months vs. 18.2 months, P=0.022) (35). Similar results were validated in ovarian cancer (36) and lung cancer (37). In our study, individual chemotherapy based on MiniPDX also showed superiority to prolong the OS and PFS of patients with GCLM, which could consider solid validation evidence for previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…Also, the study by Yang et al showed a significant benefit from the MiniPDX test than the control group in hepatocellular carcinoma (DFS: 25.8 months vs. 18.2 months, P=0.022) (35). Similar results were validated in ovarian cancer (36) and lung cancer (37). In our study, individual chemotherapy based on MiniPDX also showed superiority to prolong the OS and PFS of patients with GCLM, which could consider solid validation evidence for previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…14 Individualized chemotherapy regimens for platinumresistant ovarian cancer cases identified through the circulating tumor DNA assay and the MiniPDX drug screening system showed an overall clinical benefit of 75.0%. 15 Similarly, individualized chemotherapy regimens screened by MiniPDX have been applied for progressive non-small cell lung cancer 16 and metastatic rectal cancer. 17 Specifically, a recent study using individualized chemotherapy regimens screened by MiniPDX reported that the MiniPDX group had a significantly higher tumor-free survival rate and longer OS than the control group (receiving treatment with sorafenib) (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on patients with platinum-resistant ovarian cancer, the clinical treatment response rate guided by MiniPDX drug sensitivity detection can be as high as 75% [ 99 ]. To treat patients with non-small cell lung cancer, Chen et al confirmed that the MiniPDX-guided treatment group showed a better OS and PFS than the conventional chemotherapy group [ 100 ]. Li and colleagues verified the drug response predicted by WES, proteomics, and phosphorproteomics on the MiniPDX model and established an entire workflow from the generation of large omics datasets to in vivo drug testing models of colorectal cancer [ 101 ].…”
Section: Minipdxmentioning
confidence: 99%